The Weald & Downland Living Museum’s Saxon Hall - Lucy Hockley (EXARC Journal)
In the early days of the Weald & Downland Open Air Museum, from September 1970, there was a Saxon building on the site, which was one of only two archaeological reconstructions at the museum. This original sunken-floor Saxon building is no longer standing but, after several years in the planning, a new project saw the construction in 2015 of another Saxon building, the Saxon Hall from Steyning. The building was formally opened by the VIPs from a local school in October 2016. This article considers the development of over five years; charts the training and construction phases of the building and how plans for its interpretation have evolved, including most recently during the COVID restrictions.